PENGARUH MODAL KERJA, LEVERAGE DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR LOGAM DAN SEJENISNYA PADA BEI TAHUN 2019-2022 - Anggraini, Anisa Dewi; Pramesthi, Riska Ayu; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The aim of this research is to analyze and test the influence of working capital, leverage and liquidity on company value with profitability as an intervening variable in companies in the metal and similar sub-sector on the IDX 2019-2022. The population in this research is all Metals and Similar Sector Companies registered on the IDX in 2019-2022, a total of 17 companies. The sampling technique was determined by Purposive Sampling so that 8 samples were obtained which were used for data analysis. Data analysis and hypothesis testing in this research used the Structural Equation Model - Patial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Working capital has a negative but not significant effect on Profitability, Leverage has a significant effect on Profitability, Liquidity has a positive but not significant effect on Profitability, Working capital has a positive but not significant effect on company value, Leverage has an effect significant to company value, Liquidity has a significant negative effect on company value, Profitability has a significant negative effect on company value. The results of the indirect hypothesis test show that the variable Working capital on company value through Profitability has a positive but not significant effect, Leverage on company value through Profitability has a negative but not significant effect and Liquidity on company value through Profitability has a negative but not significant effect.